Synthesis of Bioactive Fluorinated 10H-Phenothiazines and their Sulfone Derivatives - Yogesh Dixit; Rahul Dixit; Naveen Gautam; D. C. Gautam (E-Journal of Chemistry)
The present communication deals with the synthesis of a series of fluorinated 10H-phenothiazines. 10H-phenothiazines is prepared by Smiles rearrangement of substituted 2-foramido-2´-nitrodiphenylsulfide. Substituted 2-foramido-2´-nitrodiphenylsulfide were obtained by the reaction of 2-amino-3-fluorobenzenethiol with o-halonitrobenzenes followed by formylation and 1-nitro/1-halo-10H-phenothiazines have been prepared by the reaction of substituted 2-aminobenzenethiols with reactive o-halonitrobenzene containing a nitro group or halogen atom at o-position to the reactive halogen atom directly yielded 1-nitro/1-halo-10H-phenothiazines in situ. 10H-phenothiazine sulfone derivatives have been synthesized by the oxidation of 10H-phenothiazines by 30% hydrogen peroxide in glacial acetic acid. The structure of the synthesized compounds has been characterized by spectroscopic data and elemental analysis. Antimicrobial studies of the synthesized compounds have also been included.